Biochemical Effects of Methanolic Extract of Morinda Morindoides And Morinda lucida Leaves on Lipid Profile, Bilirubin and Some Marker Enzymes - Elizabeth Abidemi Balogun; Dorcas Ibukun Akinloye (Asian Journal of Medical Research, 2016)
Objective:The present work investigated the biochemical effects of Morinda morindoides and Morinda lucida methanolic leaf extracts on lipid profile, bilirubin and some marker enzymes level in the plasma of male albino rats. Methods:Phytochemical screenings were carried out on the leaves of M.morindoides and M.lucida samples.Thirty five (35) male albino rats were divided into seven groups and administered with distilled water as the control, 50,100,200mg/Kg M.lucida methanolic extracts and 50,100,200mg/Kg of M.morindoides methanolic extracts respectively.Lipid profile, bilirubin and some marker enzymes (Alanine transaminase-ALT, Aspartate transaminase-AST, Alkaline phosphatase-ALP) assays were determined in the plasma using standard techniques. Results:Majority values of the parameter taken were not significantly (p<0.05) higher than normal control.The results from the parameters showed that both species (Morinda morindoides and Morinda lucida) have similar effects by not having pronounced adverse effect on the animals (rats), and that both species contain cardenolides and saponins. Conclusion:It was therefore concluded that M.morindoides and M.lucida could be safe at the tested dosages (50,100 and 200mg/Kg b.wt).